Electroencephalographic changes during selective attention - Ghimire, Nisha; Paudel, Bishnu Hari; Khadka, Rita; Singh, Parash Nath; Das, Asim (Asian Journal of Medical Sciences, 2014)
Background: Though many studies are conducted during attention process, it is still not clear how brain deals with attention. So we conducted a study to find out the electroencephalographic changes during selective attention. Methods: Thirty healthy right handed male students aged 23.1±2.8 yrs were asked to read congruent (red printed in red ink) and incongruent (red printed in blue ink) words printed in cards. EEG was recorded for ninety seconds during baseline (eye open) and reading of both cards. EEG epoch was analyzed by fast fourier transformation. Friedman test was used to compare EEG power spectra among baseline, congruent and incongruent reading followed by Wilcoxon’s Sign Rank Test. Data were expressed as median with inter-quartile range. Results: Compared to congruent test during incongruent test there was selective increment of theta power at Fz [36.04 (28.30-46.19) vs. 47.89 (31.65-48.1)], Cz[36.13 (27.20-46.41) vs. 45.66 (37.15-49.4)] and C4 [25.11 (19.14-30.06) vs. 30.16 (21.43-33.8)] sites but it decreased at F7 [17.88 (14.49-20.93) vs. 11.31(8.96-15.975)] and F8 [19.23 (13.61-25.79) vs. 13.95 (10.40-16.67) sites. Also during incongruent card reading, alpha1 power significantly decreased in F8 [3.39(2.63-4.63) to 2.75 (1.93-4.7)] and alpha 2 power significantly decreased in P3 6.84 [(4.88-10.46) to 5.74 (4.78-19.95)] sites. Conclusion: During selective attention, theta gets synchronized at fronto-central regions and alpha2 desynchronized at parietal regions. The theta and alpha1 at inferior frontal regions were also desynchronized in selective attention. DOI: http://dx.doi.org/10.3126/ajms.v6i2.11122 Asian Journal of Medical Sciences Vol.6(2) 2015 52-57